Implementasi Kurikulum Merdeka Mandiri Berbagi di Pendidikan Anak Usia Dini - Afriana; Nelva Rolina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The problem in this research focuses on the implementation of the Independent Curriculum, independent sharing, freeing up early childhood education units in implementing the Independent Curriculum by developing their own teaching tools. However, there are still many who are not ready because the implementation of the Independent Curriculum is different from the 2013 Curriculum in planning, implementation and evaluation. This research aims to describe the implementation of the Merdeka Mandiri Sharing Curriculum in early childhood education. This research uses a qualitative method with a case study research design. Interview, observation and documentation methods were used as techniques to collect data. The data sources used were the school principal and 5 teachers. The data analysis technique used is a descriptive qualitative interactive model including data condensation, data presentation and drawing conclusions. The research results show that the implementation of the Merdeka Mandiri Sharing Curriculum in early childhood education is carried out through three stages, namely the planning stage, implementation stage and evaluation stage. It is hoped that the implications of this research will provide insight for various related parties, especially educators, PAUD institution managers, and policy makers in increasing the effectiveness of implementing the Independent Sharing Mandiri Curriculum.